Mental Health Matters: From Cross-Cultural Perspectives - Kotera, Yasuhiro; Taylor, Elaina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue contains 25 articles about mental health considering various cross-cultural perspectives. The findings and insights obtained from these articles will help researchers, practitioners, educators, students, and the general public to better understand mental health from different perspectives. We hope that such insights will help build a more compassionate world, instead of a stigmatised one.